Mekanisme Kemitraan dan Determinan Pemilihan Pola Kemitraan Usahaternak Ayam Broiler di Kabupaten Sukabumi, Provinsi Jawa Barat - Sehabudin, Ujang; Warcito, Warcito; Iskandar, Muhammad Taufan; Hadiyat, Yayan (Institut Pertanian Bogor, 2023)
The broiler industry is the livestock industry with the highest development compared to other livestock industries. The structure of the broiler industry, which is oligopoly in nature, causes the bargaining position of livestock companies, especially integrator companies, to be very large in determining input and output prices. In contrast with broiler breeders. Farmers face production risks, as well as input and output price risks. The partnership between livestock companies and breeders is one of the efforts to overcome the problems faced by breeders. The aims of this study were (1) to find out the mechanism of broiler farming partnerships, and (2) Analyze the determinants of selecting contract farming through the nucleus-plasma scheme (PIR) (PIR) or Makloon pattern. The research was located in Sukabumi Regency, which is a broiler production center in West Java Province. The research samples were PIR and Makloon breeders with 30 farmers each, who were PT. X (PIR pattern) and PT. Y (Macloon pattern). Data analysis using the Logit Model. The results of the study show that there are differences in the partnership mechanism between the PIR pattern and the Makloon pattern, especially the provision and cost of financing the main production facilities and operational costs, as well as the components of livestock business income. Livestock income and broiler chicken population are significant determinants in choosing a partnership pattern, but with different parameter signs, the PIR pattern is positive and the Makloon pattern is negative. This means that the higher the broiler livestock business income, the farmer tends to choose the PIR pattern, conversely if the livestock population is getting bigger, the breeder tends to choose the Makloon pattern